Carbon Nanotube Pullout, Interfacial Properties, and Toughening in Ceramic Nanocomposites: Mechanistic Insights from Single Fiber Pullout Analysis. Issue 2 (9th July 2014) - Kessman, A. J.; Zhang, J.; Vasudevan, S.; Lou, J.; Sheldon, B. W.
<x xml:space="preserve">Abstract</x> While debonding and subsequent pullout at fiber‐matrix interfaces can improve fracture toughness in ceramic nanocomposites, the magnitudes of these contributions are currently the subject of ongoing debate. To provide quantitative insight into these mechanisms, ceramic matrix nanocomposites were fabricated with a polymer‐derived ceramic matrix, using multiwalled carbon nanotubes (MWCNTs) that exhibit relatively long pullout lengths. In situ micromechanical pullout tests on individual MWCNTs were used to directly measure the strength of the fiber‐matrix interface. Similar pullout lengths were also observed in bulk and thin film composites, where the fracture toughness of the composite films was measured and found to be higher than that of the matrix material. The interfacial properties from the micromechanical test and the pullout lengths from the composite films were then used to estimate the energy release rates for fiber debonding and pullout. Based on the observed MWCNT and composite failure mechanisms, these results are discussed in terms of their relation to previous estimates of toughening in MWCNT‐ceramic nanocomposites, and in terms of design possibilities for further fracture toughness improvements.